Combined exposure to PM2.5 and PM10 in reductions of physiological development among preterm birth: a retrospective study from 2014 to 2017 in China - Hu, Bo; Tang, Jie; Xu, Guangtao; Shao, Dongliang; Huang, Huafei; Li, Jintong; Chen, Huan; Chen, Jie; Zhu, Liangjin; Chen, Shipiao; Shen, Bin; Jin, Limin; et al. (Frontiers in Public Health, 2023)
Background Preterm birth (PTB) has been linked with ambient particulate matter (PM) exposure. However, data are limited between physiological development of PTB and PM exposure. Methods Trimester and season-specific PM exposure including PM2.5 and PM10 was collected from Jiaxing between January 2014 and December 2017. Information about parents and 3,054 PTB (gestational age < 37 weeks) outcomes such as weight (g), head circumference (cm), chest circumference (cm), height (cm) and Apgar 5 score were obtained from birth records. We used generalized linear models to assess the relationship between PTB physiological developmental indices and PM2.5, PM10 and their combined exposures. A binary logistic regression model was performed to assess the association between exposures and low birth weight (LBW, < 2,500 g). Results Results showed that there were 75.5% of low birth weight (LBW) infants in PTB. Decreased PM2.5 and PM10 levels were found in Jiaxing from 2014 to 2017, with a higher PM10 level than PM2.5 each year. During the entire pregnancy, the highest median concentration of PM2.5 and PM10 was in winter (61.65 ± 0.24 vs. 91.65 ± 0.29 μg/m3) followed by autumn, spring and summer, with statistical differences in trimester-specific stages. After adjusting for several potential factors, we found a 10 μg/m3 increase in joint exposure of PM2.5 and PM10 during the entire pregnancy associated with reduced 0.02 week (95%CI: −0.05, −0.01) in gestational age, 7.9 g (95%CI: −13.71, −2.28) in birth weight, 0.8 cm in height (95%CI: −0.16, −0.02), 0.05 cm (95%CI: −0.08, − 0.01) in head circumference, and 0.3 (95%CI: −0.04, −0.02) in Apgar 5 score, except for the chest circumference. Trimester-specific exposure of PM2.5 and PM10 sometimes showed an opposite effect on Additionally, PM2.5 (OR = 1.37, 95%CI: 1.11, 1.68) was correlated with LBW. Conclusion Findings in this study suggest a combined impact of fine particulate matter exposure on neonatal development, which adds to the current understanding of PTB risk and health.